Singular perturbations of finite rank. Point spectrum - Koshmanenko, V. D.; Samoilenko, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We establish necessary and sufficient conditions for the appearance of an additional point spectrum under singular perturbations of finite rank.